Organic-free, versatile sessile droplet microfluidic device for chemical separation using an aqueous two-phase system. Issue 4 (16th January 2019) - Hermann, Matthias; Agrawal, Prashant; Koch, Iris; Oleschuk, Richard
Abstract : Versatile sample preparation platform for mixing, splitting and extraction on patterned surfaces and subsequent detection by a UV/vis smartphone spectrometer. Abstract : This work presents a novel portable, versatile sessile droplet microfluidic (SDMF) device to perform liquid manipulation operations such as confining, splitting and colorimetric detection. Furthermore, chemical isolations based on an aqueous two-phase system (ATPS) for separating an analyte of choice from a complicated sample matrix can be carried out. ATPS extractions can replace conventional liquid–liquid extractions and take away the need for harmful organic solvents. Superhydrophobic (SH) surfaces were fabricated from a commercially available material, Ultra-Ever Dry® (UED®). On these SH surfaces, surface energy traps (SETs) were produced either by air plasma treatment (simultaneously) or laser micromachining (sequentially) to dock/pin an ATPS containing droplet onto the surface. Splitting of droplets or removing a precise volume of the top phase from a pinned extraction system was achieved with a sandwich-chip approach. For this, an additional SET patterned substrate was placed on top of the droplet and subsequently lifted. This multipurpose platform was used to isolate Cd from a mixture of several other metal ions ( i.e. Mn, Ni, Cu, Pb, Fe) for its subsequent interference-free detection. An ATPS consisting of sodium sulfate and polyethylene glycol (PEG) as phase forming components and potassium iodine as extractant allowed separation of cadmium with an extraction efficiency of q (Cd 2+ ) = 98.5%. Using a portable, cost-effective, smartphone-based UV/vis spectrometer, Cd was detected with a LoD of 3.4 ppm. Alternatively, the multipurpose platform can also be used as sampling platform for a benchtop UV/vis spectrometer, where a LoD of 0.53 ppm was obtained. Potential applications of the presented platform include sample preparation and separation that can be achieved by aqueous two-phase extractions, such as proteins, antibodies, DNA, cells, organic molecules and metal ions.